(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The different data dealt with by the author suggest that the Iberian language had a typical agglutinative accent. All or most Iberian words had a fixed accent probably falling on the last syllable. Linguistic reconstruction typology may be of help for philologists especially when there is an apparent gap in important data as is the case of Iberian.